Family Support Increases Self-Esteem in Rehabilitation Stroke Patients - Ferishandy Bagaskara; Nina Indriyawati; Suharto Suharto (JENDELA NURSING JOURNAL, 2021)
Background: the number of hemorhagic and non-hemorhagic stroke increase significantly year by year and the number of rehabilitation stage stroke patient that has the problem of family support is still high.Purpose: this study aims to determine the corellation between the level of family support and the level of self-esteem in stroke patients in the rehabilitation stage.Methods: the type of research design that researcher used is a correlation test design. The approaching methods that used by the researcher is a cross-sectional study. The researcher uses purposive sampling based on the criteria that researcher made. To  obtain the data researcher uses 2 questionaire, that is Family Support Questionaire and RSES (Rosenberg Self-Esteem Scale)Results: the result of this research is the value of Sig. (2-tailed) Spearman's rank test of family support with the level of self-esteem of stroke patients in the rehabilitation stage is 0.000 or p 0.05. Next is the value of Sig. (2-tailed) Spearman rank test of emotional support and appreciation with the self-esteem level of stroke patients in the rehabilitation stage is 0.000 or p 0.05, instrumental support with self-esteem is 0.000 or p 0.05, and informational support with self-esteem level. esteem is 0.01 or p 0.05.Conclusion: there is a corellation between family support both in general and in the aspects such as emotional, appreciation, instrumental, and informational aspects with the level of self-esteem in stroke patients in the rehabilitation stage.